2014
DOI: 10.4028/www.scientific.net/amr.887-888.384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives on the Surface Layers of Boronized TC4 Titanium Alloys

Abstract: The boronizing experiments on the surface of Ti-6Al-4V (TC4) titanium alloys were based on solid powder method. Different additives were added into the boronizing agent. The morphologies of surface layers on titanium alloys were observed in scanning electron microscopy (SEM). The phase compositions of boronized layers were analyzed by X-ray diffraction (XRD). The wear resistance properties of boronized TC4 were determined by the friction and wear testing machine. The results showed that all the boronized layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, the related experimental studies were conducted under protective gas atmospheric conditions and/or using expensive equipment. 32,[38][39][40][41][42][43] As a result of the present study, it can be concluded adding aluminum to the solid boriding media prevented surface fractures and decreased the oxidation caused by atmospheric gases. Consequently, it was possible to obtain an undamaged boronized titanium surface via solid-state boriding under atmospheric conditions.…”
Section: Resultssupporting
confidence: 58%
“…However, the related experimental studies were conducted under protective gas atmospheric conditions and/or using expensive equipment. 32,[38][39][40][41][42][43] As a result of the present study, it can be concluded adding aluminum to the solid boriding media prevented surface fractures and decreased the oxidation caused by atmospheric gases. Consequently, it was possible to obtain an undamaged boronized titanium surface via solid-state boriding under atmospheric conditions.…”
Section: Resultssupporting
confidence: 58%
“…The friction coefficient of Ti6Al4V fluctuated relatively violently, and the Ti6Al4V substrate underwent plastic deformation and formed adhesion points with steel ball under high contact stress, which were constantly sheared and regenerated, resulting in the fluctuation of the friction coefficient (Wang et al , 2014).…”
Section: Resultsmentioning
confidence: 99%